Nanobiosystems : processing, characterization, and applications : 12-14 August 2008, San Diego, California, USA - Heckman, Emily M.; Singh, Thokchom B.; Yoshida, Jun'ichi, 1948- (Washington : Society of Photo Optical, 2008)
53